Ownership and Participation in Local–Global Partnerships: The Recovery of Shelter and Settlements after Humanitarian Crises. (26th December 2019) - Babister, Elizabeth
Abstract: Local actors affected by humanitarian crises, including disasters and conflict, often attract the support of global actors with engineering resources to support the recovery of their shelter and settlements. Global initiatives increasingly prioritise the agency of local actors and the concept of local participation following humanitarian crises, and a critical mass of evidence of the role of local actors in the recovery of their shelter and settlements has now emerged. This study reviews this body of knowledge and considers its implications on the global humanitarian policy framework. Data have been collected from emerging literature on the recovery of shelter and settlements and extended with sampling cases of 25 crises over the past two decades. This study finds that for the successful recovery of shelter and settlements, the participation of affected households must prioritise their ownership of the recovery process, rather than simply their level of involvement. Furthermore, a focus on local participation appears to be most successful when tailored to the capacity households have to contribute and the shape of their plans for recovery. At the level of global humanitarian policy, a shift in priorities is required if local ownership and successful recovery is to be achieved. These priorities include more broadly assessing local capacity during the immediate aftermath of crisis, paired with systematically funding beyond the first 12 months after a crisis with adaptive funding instruments. The focus of this paper is the recovery of shelter and settlements, but the analysis could be used more generally in other contexts where the need for rapid global response with financial, technical and engineering knowledge coincides with the need to work with local social, political and technical knowledge and experiences.